Nigeria at hundred: teachers’ and students’ perception of the adequacy of upper basic education social studies curriculum as a tool for national security (2015)
Nigeria today is besieged by an array of social, economic and political problems which has been attributed to citizenry low level of civility. This resulted to security threats in the nation, despite, the inclusion of Social studies in the curriculum. This study investigated the perception of teachers and students on the adequacy of upper basic education social studies curriculum as a tool for national security. Three research questions were answered and three hypotheses tested to guide this study. This study adopted a descriptive survey design. A total of 110 social studies teachers and 300 junior secondary school students were selected using simple random sampling technique from Akinyele and Ibadan North Lbcal Government Areas of Oyo State. Two instruments tagged "Teachers Questionnaire on Social Studies as a tool for national security (TSNS) (r=0.71) and Students Questionnaire on Social Studies as a tool for national security” (SSNS) (r=0.78) were used to collect data for the study. The estimated reliability coefficients of the instruments were found to be 0.61 for teachers and 0.68 for students. Data were analysed using simple percentage, mean, standard deviation, and t-test at 0.05 level of significance. Findings revealed that teachers had low perception of upper basic social studies curriculum as a tool for national security while the students had a higher perception of upper basic social studies curriculum as a tool for national security. Also, there was a significant difference between the teachers’ and students’ perception of the adequacy of upper basic social studies curriculum as a tool for national security. It is recommended, among other things that social studies teachers should be exposed to more knowledge on national security concepts. While seminars and workshops should be organised for Social Studies teachers to enable them use the teaching of Social Studies to achieve national security.